POTENTIAL ENERGY OF OCEAN CURRENT FOR ELECTRIC POWER GENERATIONIN COASTAL AREAS OF EAST FLORES, NTT - Ai Yuningsih; Achmad Masduki (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2011)
The electrical energy is one of the important needs for coastal communities particularly in small islands that has not reached by national electricity network. In order to fulfill this particular electricity needs, we do variety diversification efforts, such as the utilization of the ocean currents. The purpose of this survey is to recognize the morphology of seafloor and characteristic of hydro-oceanography as a fixed reference location in using the current energy. The study area is in the Larantuka Strait between Flores and Adonara islands which is part of the Flores Strait, East Nusatenggara Province. The methods of this study are current measurements, tidal and meteorological parameter observations, condition of coastal morphology and seafloor of the study area. The result show that, the location for turbine position is in area with relatively gentle slope morphology at a 20 meters water depth and it is close to local community. Based on the analysis of ADCP mobile current measurement, the minimum current velocity is 0.004 m/sec and maximum 3.68 m/sec. Whereas, from the ADCP static measurements the current velocity is from 0.002 m/sec to 2.83 m/sec. This condition is closely related to the semi-diurnal tide type in the study area, with two pairs of flood and web events within 24 hours. Therefore, the results of ocean current energy analysis indicate that the study area is very potential for using as a power plant location.Keywords: potential energy of ocean currents, power plants, energy diversification, Larantuka Strait, East Flores